Electrochemical Radical Borylation of Aryl Iodides. Issue 4 (26th February 2019) - Hong, Junting; Liu, Qianyi; Li, Feng; Bai, Guangcan; Liu, Guoquan; Li, Man; Nayal, Onkar S.; Fu, Xuefeng; Mo, Fanyang
Summary of main observation and conclusion: Herein, we report the first electrochemical strategy for the borylation of aryl iodides via a radical pathway using current as a driving force. A mild reaction condition allows an assorted range of readily available aryl iodides to be proficiently converted into synthetically valuable arylboronic esters under transition metal catalyst‐free conditions. Moreover, this method also shows good functional group tolerance. Initial control mechanistic experiments reveal the formation of aryl radical as a key intermediate and the current plays an important role in the generation of radical intermediate. Abstract : The first electrochemical strategy for the radical borylation of aryl iodides is reported in this paper. The significant promoting effect of current in the aryl radical generation is revealed by EPR studies.